2022
DOI: 10.1002/hbm.25770
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection of neuromelanin and iron in the midbrain nuclei using a magnetic resonance imaging‐based brain template

Abstract: Parkinson disease (PD) is a chronic progressive neurodegenerative disorder characterized pathologically by early loss of neuromelanin (NM) in the substantia nigra pars compacta (SNpc) and increased iron deposition in the substantia nigra (SN). Degeneration of the SN presents as a 50 to 70% loss of pigmented neurons in the ventral lateral tier of the SNpc at the onset of symptoms. Also, using magnetic resonance imaging (MRI), iron deposition and volume changes of the red nucleus (RN), and subthalamic nucleus (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…2,[28][29][30] In most previous studies, measured bilateral SN volumes range from 110 to 700 mm 3 , showing a high degree of variation. 3,10,30,31 In one previous paper investigating susceptibility-related MRI, average SN volumes of 541 and 621 mm 3 for HC and PD, respectively, were reported from manually segmented masks surrounding the hypointense area in T 2 * -weighted images. 3 By comparison, the bilateral SN volumes in our study ranges from 1128 to 1527 mm 3 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2,[28][29][30] In most previous studies, measured bilateral SN volumes range from 110 to 700 mm 3 , showing a high degree of variation. 3,10,30,31 In one previous paper investigating susceptibility-related MRI, average SN volumes of 541 and 621 mm 3 for HC and PD, respectively, were reported from manually segmented masks surrounding the hypointense area in T 2 * -weighted images. 3 By comparison, the bilateral SN volumes in our study ranges from 1128 to 1527 mm 3 .…”
Section: Discussionmentioning
confidence: 99%
“…One recent study reported the segmentation of SN using QSM data by advanced image analysis with DSC values of 0.75 and 0.76 in left and right SN, respectively 11 . Different neuromelanin‐ and iron‐containing midbrain nuclei were also segmented using a template of the brain from QSM data and achieved a DSC of 0.85 and 0.87 for neuromelanin‐ and iron‐containing SN, respectively 10 . 3D SN segmentation on neuromelanin‐sensitive MRI and SWI using a V‐net convolutional neural network yielded an average DSC in five‐fold cross‐validation of 0.7 8 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations